2019
DOI: 10.7759/cureus.5112
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing the Promise of Omadacycline in a Resistant, Non-tubercular Mycobacterial Pulmonary Infection

Abstract: The non-tubercular mycobacterium, Mycobacterium abscessus (M. abscessus), is a resistant, opportunistic pathogen that causes lung infections that are not curable, but which can be controlled with appropriate antibiotic regimens. A new broad-spectrum tetracycline analog called omadacycline was approved in 2018 in the United States for the treatment of bacterial, community-acquired pneumonia and acute skin infections. We discuss a case to assess the effect of this novel antibiotic in the management of a nefariou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…In the past few years, in vitro studies of omadacycline have reported low MICs against M. abscessus and therefore offer promising potential against this bacterium ( 21 23 , 25 ). Additionally, recent real-world case reports and case series have reported promising clinical outcomes with regimens containing omadacycline in treating M. abscessus lung disease ( 27 , 59 61 ). These observations have warranted evaluation in a preclinical model that permits efficacy determination of omadacycline alone against multiple M. abscessus isolates in a controlled laboratory setting.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, in vitro studies of omadacycline have reported low MICs against M. abscessus and therefore offer promising potential against this bacterium ( 21 23 , 25 ). Additionally, recent real-world case reports and case series have reported promising clinical outcomes with regimens containing omadacycline in treating M. abscessus lung disease ( 27 , 59 61 ). These observations have warranted evaluation in a preclinical model that permits efficacy determination of omadacycline alone against multiple M. abscessus isolates in a controlled laboratory setting.…”
Section: Discussionmentioning
confidence: 99%
“…In the first 3 studies discussed above, omadacycline MICs correlated well with tigecycline MICs. Despite the growing literature of favorable in vitro data for M abscessus , there has been only 1 report of omadacycline clinical use in this situation [ 29 ]. This case series provides the most clinical data published on the use of omadacycline for M abscessus disease to date.…”
Section: Discussionmentioning
confidence: 99%
“…Based on available evidence to date, oral omadacycline thus represents an attractive option for replacement of intravenous tigecycline in drug regimens to treat M. abscessus pulmonary infections. However, since the clinical efficacy of omadacycline in M. abscessus infections is limited to a single case report to date, 130 further studies are required to test this hypothesis.…”
Section: Repurposable Drugs Versus M Abscessus Complex: Play To Losementioning
confidence: 99%